The Differences of Batubara and Tanjung Pura Malay Language from Phonological Aspects - Doni Efrizah (Budapest International Research and Critics University, 2022)
This study aims to discuss the differences between Batu Bara Malay and Tanjung Pura Malay in terms of phonological aspects. There are many differences in the vocabulary used in the two Malay languages, both in pronunciation and writing. For this reason, it is necessary to describe the differences in the vocabulary of Batubara Malay and Tanjung Pura Malay. These words have the same meaning but are pronounced differently. This study uses an approach that focuses on the designation of the same meaning but different pronunciation. This study uses data in the form of basic Malay vocabularies based on sources from Batu Bara Malay and Tanjung Pura Malay communities which are translated into Indonesian. The instrument used in data collection in this study was a recording device used to interview several natives of Batu Bara and Tanjung Pura area who have a distinctive Malay accent. The method used in this research is listening and recording method and the research also use the technique of listen and write. This study uses a method that is presented informally. The results of this study are the differences between Batu Bara Malay and Tanjung Pura Malay phonologically.